Final Review of the Application of the SCOR Model: Supply Chain for Biodiesel Castor – Colombia Case - Salazar, Fernando; Caro, Martha; Cavazos, Judith (Journal of Technology Innovations in Renewable Energy, 2012)
This paper presents the final analysis on the process of characterizing the supply chain for Biodiesel Castor, made with the application of the SCC, SCOR Model, showing the strengths and weaknesses in the design of a strategic plan and logistics, as an important aspect in the search for alternatives, where tools such as SCOR and other applications or methodologies to characterize supply chains, may provide support for effective decision making, which somehow guarantees progress and development of production systems. This application, as a methodological tool, led to the identification of the different variables and operations that make up the supply chain processes such as obtaining Biodiesel from Castor, which determined what are the KPI´s of this chain, a determining factor for the validation of logistics Biodiesel process operations in order to strengthen and identify disconnects. In an increasingly globalized world, where the strength and competitiveness are defined by the effective management of the supply chain that enables better delivery of customer service and value chain through the management of information flows, product and financial flows, such management potentiates the compete successfully in today’s markets, for the result produced by the combination of the objectives of supply chain and implementing best practice methodologies.